Primary Cultures from Rat Dorsal Root Ganglia: Responses of Neurons and Glial Cells to Somatosensory or Inflammatory Stimulation. (1st December 2018) - Leisengang, Stephan; Ott, Daniela; Murgott, Jolanta; Gerstberger, Rüdiger; Rummel, Christoph; Roth, Joachim
Highlights: Cultured DRG neurons respond to somatosensory stimulation with Ca 2+ signals. LPS enhances capsaicin-evoked Ca 2+ signals' DRG primary cultures. LPS-stimulation induces various mediators of inflammation in cultured DRG. Cisplatin reduces numbers of satellite glial cells, macrophages and inflammation. Stimulus-induced Ca 2+ signals in DRG neurons are not impaired by cisplatin treatment. Abstract: Primary cultures of rat dorsal root ganglia (DRG) consist of neurons, satellite glial cells and a moderate number of macrophages. Measurements of increased intracellular calcium [Ca 2+ ]i induced by stimuli, have revealed that about 70% of DRG neurons are capsaicin-responsive nociceptors, while 10% responded to cooling and or menthol (putative cold sensors). Cultivation of DRG in the presence of a moderate dose of lipopolysaccharide (LPS, 1 µg/ml) enhanced capsaicin-induced Ca 2+ signals. We therefore investigated further properties of DRG primary cultures stimulated with 10 µg/ml LPS for a short period. Exposure to LPS for 2 h resulted in pronounced release of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) into the supernatants of DRG cultures, increased expression of both cytokines in the DRG cells and increased TNF immunoreactivity predominantly in macrophages. We further observed an accumulation of the inflammatory transcription factors NF-IL6 and STAT3 in the nuclei of LPS-exposed DRG neurons and macrophages. In the presence of the cytotoxic agent cisplatin (5 or 10 µg/ml), the number of macrophages was decreased significantly, the growth of satellite glial cells was markedly suppressed, but the vitality and stimulus-induced Ca 2+ signals of DRG neurons were not impaired. Under these conditions the LPS-induced production and expression of TNF-α and IL-6 were blunted. Our data suggest a potential role for macrophages and satellite glial cells in the initiation of inflammatory processes that develop in sensory ganglia upon injury or exposure to pathogens.